Trend Analysis of Profitability Ratio of Indonesian Sharia Bank Using Semi Average Method - Husna, Hidayatul; Lubis, M Zaky Mubarak; Binti Mohamad, Zam Zuriyati (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
One of the key ratios in a bank that is essential is the profitability ratio. This ratio, which can be explained by ROA, ROE, and NIM, is related to the bank's profitability. Customers will use a strong profitability value as a point of comparison. Based on data from 2016–2023 taken from the annual report, this study was carried out in Bank Muamalat and employed a trend analysis to see the development of profitability ratios at Bank Muamalat in 2024–2026. Semi-average analytical approach for trend analysis. The analysis revealed that Bank Muamalat's general trends decreased in all three ratios. This may serve as a reminder to the management to adopt policies that are appropriate for the business. However, Bank Muamalat customers can also utilize these results as a guide to make future financial decisions.